A Discursive Review of Recent Development and Patents on Glycerosomes - Singh, Ragini; Zeeshan, Fatima; Srivastava, Dipti; Awasthi, Himani (Recent Patents on Nanotechnology, 2023)
Background: To achieve a target-based drug delivery with minimal side effects, novel drug delivery systems are being continuously explored. Vesicular systems are one such system that can ameliorate the bioavailability of the encapsulated drug by delivering the drug at the targeted site and can minimize the side effect. Objective: The objective of this patent review is to provide a vivid description of glycerosomes and their applications. Glycerosomes are sphere-shaped versatile vesicles consisting of one or more phospholipid bilayers similar to liposomes but contain a high concentration of glycerol, which modifies the liposome bilayer fluidity. Glycerosomes can encapsulate both hydrophobic and hydrophilic drugs, which makes them the promising vehicle in the field of drug delivery. Conclusion: Most of the glycerosome formulations prepared were targeted for topical delivery and in particular, a cutaneous route where they have shown promising results. These vesicles are biocompatible and due to the high glycerol concentration, they have improved spreadability and penetrability. It is therefore imperative to explore the other topical routes such as ocular, vaginal, nasal, and rectal for delivery of drugs.
Keywords: topical delivery